Improving the quality of life in menopausal women. An overview of menopausal hormone therapy possibilities - О. I. Lisitsyna (Медицинский совет, 2019)
Menopause is a woman’s journey through the transitional period of life. Along with estrogen deficiency, age-related changes in this period include relative hyperandrogenism and reactivation of renin-angiotensin-aldosterone system (RAAS). These processes can lead to both the manifestation of clinical estrogen-deficient symptoms and the increase in metabolic disorders and cardiovascular diseases. The task of every obstetrician-gynecologist is to provide appropriate professional advice on issues related to the specified period. To date, prescribing MHT in postmenopausal women, along with the mandatory compliance with a healthy lifestyle, is consistent with the general principles of maintaining women’s health and improving the quality of life. The authors of this work provide an overview of possibilities for MHT for the treatment and prevention of conditions associated with estrogen deficiency in menopause.